Morbi - mortalidad por shock séptico en pacientes menores de 5 años atendidos en el Hospital de Apoyo Iquitos “César Garayar García” año 2020 – 2021 - Quispe Ticuña, Hilda (2024)
Sepsis is a potentially fatal organ dysfunction caused by an unregulated immune response to infection. It affects millions of people worldwide and has a mortality rate of 17-34%. Since 2002, the American College of Critical Care Medicine Pediatric Advanced Life Support has published guidelines for sepsis treatment, but many studies show low compliance rates due to lack of protocols and differences in hospital realities. The objective of the Campaña sobreviviendo a la sepsis: directrices internacionales para el manejo de la sepsis y el shock séptico 2021 is to identify early diagnosis and appropriate treatment in the first hours post sepsis to improve results and reduce hospital mortality and prevent sepsis and organ dysfunction. Factors associated with morbi-mortality in pediatric patients with sepsis and shock séptico include socio-demographic factors, epidemiological profiles, clinical characteristics, initial management, and complications. The study aims to inform healthcare personnel and incorporate guidelines and protocols for early diagnosis and timely management of sepsis and shock séptico in pediatric patients.